1993
DOI: 10.1002/kin.550250605
|View full text |Cite
|
Sign up to set email alerts
|

New substrates in the ferroin‐catalyzed bromate system in aqueous‐organic mixed media

Abstract: A large number of substrates have hitherto been employed in the Belousov-Zhabotinsky (B-Z) oscillatory system in pure aqueous medium. A systematic study of aromatic bromate oscillators is limited by solubility problem relating to the compounds and the brominated derivatives. The use of aqueous-organic mixed media for the oscillatory study is found to be highly useful for the study of water insoluble substances. A comparative study of the oscillatory behavior of gallic acid as substrate in pure aqueous as well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
1

Year Published

1994
1994
2002
2002

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 12 publications
1
9
1
Order By: Relevance
“…This can be attributed to the fused ring structure of flavones. The mechanism of the catalyzed bromate system in mixed media is found to be the same as that in pure aqueous medium, even though the oscillatory characteristics are altered in the presence of an organic solvent (15). As these substrates are not water soluble, a comparison of the oscillatory behaviour in mixed medium and pure aqueous medium could not be made.…”
Section: Results and Discussion (A) Gallic Acid As Substratementioning
confidence: 89%
See 2 more Smart Citations
“…This can be attributed to the fused ring structure of flavones. The mechanism of the catalyzed bromate system in mixed media is found to be the same as that in pure aqueous medium, even though the oscillatory characteristics are altered in the presence of an organic solvent (15). As these substrates are not water soluble, a comparison of the oscillatory behaviour in mixed medium and pure aqueous medium could not be made.…”
Section: Results and Discussion (A) Gallic Acid As Substratementioning
confidence: 89%
“…(ii) Since it is water soluble, the study would enable a comparison of its dynamic behaviour in different mixed media as well as in pure aqueous medium. In fact, aqueous-organic media have been used successfully in the ferroin-catalyzed as well as the uncatalyzed bromate systems with gallic acid as substrate (15,16).…”
Section: Results and Discussion (A) Gallic Acid As Substratementioning
confidence: 99%
See 1 more Smart Citation
“…As far as antioxidants more lipophilic than those studied here are concerned, it is our intention to study the behavior of the BR reaction and inhibitory effects in mixed organic/aqueous media (20% (v/v)) with other organic solvents as i-PrOH, THF, and MeCN where it has been reported that the well-known Belousov [21]-Zhabotinsky [22] reaction can occur [23].…”
Section: 2mentioning
confidence: 99%
“…spectrophotometry [5,6], potentiometry [7], and thermometry [7][8][9][10]. In the recent past, a number of organic and mixed substrates have been used to obtain more informations regarding the mechanism of such reactions [11][12][13][14][15][16][17][18]. In our earlier communication [19], we have reported the temperature oscillation of bromate/gallic acid/sulfuric acid system as a function of bromate concentration with and without ferroin in a calorimeter with elaborate thermodynamic and mechanistic analysis of the results.…”
Section: Introductionmentioning
confidence: 99%